2018
DOI: 10.3126/jnhrc.v16i1.19359
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Level of Patients Undergoing Oral Surgical Procedures

Abstract: Background: Evidences on dental anxiety scale are essential in dental practice for better service delivery. The main objective of this study was to determine the anxiety level of patients undergoing oral surgical procedures and explore its associated factors.Methods: This was a cross sectional study enrolling 142 patients. Semi structured questionnaire based on Corah’s dental anxiety scale was prepared and administered to gather information. Descriptive statistics, chi- square test and independent t- test were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The findings of study showed that 90.54 % of respondents had very low anxiety, 6.75% had moderate anxiety and 2.70% had severe anxiety. The study conducted by Acharya et al 9 in Kathmandu, Nepal shows 70% had very low anxiety, 23.20% had moderate anxiety and 7% had severe anxiety which is only comparable with this present study…”
Section: Discussionsupporting
confidence: 87%
“…The findings of study showed that 90.54 % of respondents had very low anxiety, 6.75% had moderate anxiety and 2.70% had severe anxiety. The study conducted by Acharya et al 9 in Kathmandu, Nepal shows 70% had very low anxiety, 23.20% had moderate anxiety and 7% had severe anxiety which is only comparable with this present study…”
Section: Discussionsupporting
confidence: 87%
“…Demographic differences among patients can affect differences in the degree of dental anxiety. Acharya et al 12 and Udoye et al 13 have reported significant differences in dental phobia according to sex and age, using the DAS questionnaire. Similar results were also reported in a study by Appukuttan et al 14 , which used the Tamil version of the modified DAS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Every surgical procedure may lead to apprehension and anxiety, and good sedation is effective to reduce pain and anxiety for improved patient cooperation and satisfaction. [ 21 25 ] The comparative evaluation of midazolam and dexmedetomidine is conducted by the intravenous or intranasal route. One study compares intravenous propofol with fentanyl and midazolam with fentanyl for third molar surgery and finds no significant reduction in vital parameters (SpO 2 , pulse rate, and blood pressure).…”
Section: Discussionmentioning
confidence: 99%